Participatory budgeting as an effective tool for sustainable development of communities - Syzonenko, Olena; Сизоненко, Олена Василівна; Сизоненко, Елена Васильевна (Europäische Wissenschaftsplattform, 2019)
Ensuring transparency of the budget process and public participation in its organization envisages the timely and accurate disclosure of information on the use of budget funds, as well as the ability of the public to participate in the formation and implementation of the budget, which is an indisputable sign of democracy in many countries around the world.
Keywords: budget; communitie; budgeting